Асимптотичні методи дослідження моделей із швидкими змінними - Омельяненко, А. В. (ХНУРЕ, 2024)
The purpose of the work is to study the problem and solve the problems of modeling the restoration of the system and the behavior of the human operator in the presence of harmful and dangerous external influences and man-made disasters. Human-machine systems (HMS) also have an "external environment" subsystem, which includes catastrophic and harmful effects of the environment, commonly called the "Human-Machine-Environment system".
Keywords: людино-машинна система; метод Паде-апроксимації